PENGGUNAAN METODE KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SDN 002 BAGAN BESAR PADA MATA PELAJARAN MATEMATIKA - Nurlela (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2015)
This study titled STAD type of cooperative use to improve student learning outcomes Learning Math Class V SDN 002 Bagan Besar. This study aims to increase in activity and the results of student learning using STAD type of cooperative learning in Math Class V student of SDN 002 Bagan Besar Kecamatan Bukit Kapur Dumai. The method used is descriptive method with the form of classroom action research study. The results obtained are student activity. Shows that the use of cooperative methods can enhance the activity and results of students of class V SDN 002 Bagan Besar Kecamatan Bukit Kapur Dumai.